2015
DOI: 10.1111/nhs.12242
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of health risk behavior, awareness, and health benefit beliefs of health science and non‐health science students: An international study

Abstract: This study determines the differences in health risk behavior, knowledge, and health benefit beliefs between health science and non-health science university students in 17 low and middle income countries. Anonymous questionnaire data were collected in a cross-sectional survey of 13,042 undergraduate university students (4,981 health science and 8,061 non-health science students) from 17 universities in 17 countries across Asia, Africa, and the Americas. Results indicate that overall, health science students h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 29 publications
(52 reference statements)
4
38
0
5
Order By: Relevance
“…Nutritional habits Regarding nutritional habits and gender differences, the herein results are also in line with those found in a Canadian university community context [25] and in the literature in general [26], Indeed, it has been found that male students generally exhibit less desirable food habits, such as lack of V&F consumption and skipping breakfast. Breakfast consumption has been associated with a lower likelihood of being overweight [27].…”
Section: Discussionsupporting
confidence: 79%
“…Nutritional habits Regarding nutritional habits and gender differences, the herein results are also in line with those found in a Canadian university community context [25] and in the literature in general [26], Indeed, it has been found that male students generally exhibit less desirable food habits, such as lack of V&F consumption and skipping breakfast. Breakfast consumption has been associated with a lower likelihood of being overweight [27].…”
Section: Discussionsupporting
confidence: 79%
“…Overall, the negative health behaviors and lifestyles could present multiple health risks, especially the threat from chronic diseases and/or severe health conditions, to the participants in the future [2,3,49], depending on the intensity of their current health behaviors, risks, and lifestyles and the changes in behaviors and lifestyles in the future. e health risks associated with economic underdevelopment, that is, according to the family status of a majority of the respondents, e.g., 67.3% of them reported as not very well-off or quite poor, may have a negative repercussion on or implications for their diet and quality of the food consumed, among others.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses and nursing students work closely with patients in providing direct care and serving as patient advocates (Hyland, 2002), and expectations exist for nurses and nursing students to be role models to patients and families and exemplars of good health practices (Darch, Baillie, & Gillison, 2017), thus setting them apart from other health professions and university students. Nursing and other health-related students may acquire skills and knowledge in health and promotion practices during their education/training, increasing their awareness of health behavior risks (Peltzer, Pengpid, Yung, Aounallah-Skhiri, & Rehman, 2016). However, this knowledge is often not applied to their personal behavior, and they have similar health behavior risk as other students (Horneffer, 2006;Peltzer et al, 2016;Stark, Manning-Walsh, & Vliem, 2005).…”
Section: Studentsmentioning
confidence: 99%
“…Nursing and other health-related students may acquire skills and knowledge in health and promotion practices during their education/training, increasing their awareness of health behavior risks (Peltzer, Pengpid, Yung, Aounallah-Skhiri, & Rehman, 2016). However, this knowledge is often not applied to their personal behavior, and they have similar health behavior risk as other students (Horneffer, 2006;Peltzer et al, 2016;Stark, Manning-Walsh, & Vliem, 2005).…”
Section: Studentsmentioning
confidence: 99%